Trauma, substance use, and mental health symptoms in transitional age youth experiencing homelessness. Issue 3 (23rd March 2020) - Dawson‐Rose, Carol; Shehadeh, Deena; Hao, Jennifer; Barnard, Jasmine; Khoddam‐Khorasani, Ladan (Ladi); Leonard, Adam; Clark, Kristen; Kersey, Eva; Mousseau, Haley; Frank, Julie; Miller, Aaron; Carrico, Adam; et al.
Abstract: Objective: This descriptive study examined the prevalence and correlates of trauma, substance use, and mental health symptoms in homeless transitional age youth (TAY) in San Francisco. Design & Sample: One hundred homeless TAY were recruited from a community‐based organization to complete a survey on trauma, mental health symptoms, and substance use. Measurements: We used these measures: National Institute on Drug Abuse (NIDA)‐Modified Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) for frequency and risk level of substance use; the 10‐item Adverse Childhood Experiences (ACEs) for prevalence of trauma; the Post‐traumatic Stress Disorder Checklist for DSM‐5 for post‐traumatic stress disorder (PTSD) symptoms; Center for Epidemiologic Studies Depression Scale for depression symptoms; and Generalized Anxiety Disorder 7‐item for anxiety symptoms. Results: Almost all ( n  = 98) participants experienced at least one ACE during childhood, and 77% experienced four or more. Most participants (80%) reached the diagnostic threshold for PTSD, 74% for depression, and 51% for moderate anxiety. Symptoms of PTSD, anxiety, and depression were all significantly correlated with use of opioids and stimulants. Conclusion: Trauma, and co‐occurring substance use and mental health problems are prevalent among homeless TAY. Individual‐ and community‐level interventions are needed to address and improve the health of this population.